2018
DOI: 10.5644/ama2006-124.226
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Gender on the Cortical Width of the Lower Border of the Mandible and the Mandibular Cortical Index

Abstract: <p><strong>Objective.</strong> To evaluate the influence of gender on the mental index (MI) and  the mandibular cortical index (MCI).</p><p><strong>Methods.</strong> In this study, there were 120 subjects (43 male and 77 female subjects), who had undergone a dental panoramic radiograph examination for the needs of diagnosis and future treatment planning. MI and MCI were determined by orthopantomograph.</p><p><strong>Results.</strong> There was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Alias et al 1 conducted a retrospective review of 79 subjects (48 male, 31 female) and demonstrated that the male gender had a significant association with a square-shaped chin, prominent muscle markings, and everted gonial flare. Kamber-Cesir et al 4 measured the mental indices, defined as cortical thickness inferior to the mental foramen, in 120 subjects and found that males had a higher mental index than females. Consistent with the work of Alias et al, 1 our data demonstrate that the male mandible is in general, larger in height and width and has a more acute angle with an average difference of about 7.79 mm, 8.20 mm, and 4.43 degrees, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alias et al 1 conducted a retrospective review of 79 subjects (48 male, 31 female) and demonstrated that the male gender had a significant association with a square-shaped chin, prominent muscle markings, and everted gonial flare. Kamber-Cesir et al 4 measured the mental indices, defined as cortical thickness inferior to the mental foramen, in 120 subjects and found that males had a higher mental index than females. Consistent with the work of Alias et al, 1 our data demonstrate that the male mandible is in general, larger in height and width and has a more acute angle with an average difference of about 7.79 mm, 8.20 mm, and 4.43 degrees, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…3 Male mandibles tend to have a squarer appearance, thicker cortical width below the mental foramen, everted gonial angle, and bulkier masseter musculature compared with females. 1,[4][5][6] These anatomic differences are essential in establishing surgical targets for gender-affirming facial procedures, yet there is a paucity of recent literature describing the normative anatomy of the mandible by sex. A mandible shape that is incongruent with an individual's gender identity can be a barrier to living out their self-experienced gender and negatively impact their psychosocial well-being and quality of life.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that in men, the volume and thickness of the masseter are significantly greater compared to women, and the mandibular angle is also more acute in men (25,26) . These differences begin in childhood and persist into adulthood.…”
Section: Final Considerationsmentioning
confidence: 99%